PAPAS promotes differentiation of mammary epithelial cells and suppresses breast carcinogenesis - Sijia Ren; Feng Bai; Viviane Schnell; Clara Stanko; Muriel Ritsch; Tino Schenk; Emanuel Barth; Manja Marz; Bin Wang; Xin-Hai Pei; Holger Bierhoff (Cell Reports, 2024)
Summary: Extensive remodeling of the female mammary epithelium during development and pregnancy has been linked to cancer susceptibility. The faithful response of mammary epithelial cells (MECs) to hormone signaling is key to avoiding breast cancer development. Here, we show that lactogenic differentiation of murine MECs requires silencing of genes encoding ribosomal RNA (rRNA) by the antisense transcript PAPAS. Accordingly, knockdown of PAPAS derepresses rRNA genes, attenuates the response to lactogenic hormones, and induces malignant transformation. Restoring PAPAS levels in breast cancer cells reduces tumorigenicity and lung invasion and activates many interferon-regulated genes previously linked to metastasis suppression. Mechanistically, PAPAS transcription depends on R-loop formation at the 3′ end of rRNA genes, which is repressed by RNase H1 and replication protein A (RPA) overexpression in breast cancer cells. Depletion of PAPAS and upregulation of RNase H1 and RPA in human breast cancer underpin the clinical relevance of our findings.